2022
DOI: 10.1111/1365-2664.14233
|View full text |Cite
|
Sign up to set email alerts
|

Habitat availability alters the relative risk of a bovine tuberculosis breakdown in the aftermath of a commercial forest clearfell disturbance

Abstract: 1. Human modification of landscapes and associated disturbances may facilitate the emergence and spread of zoonotic diseases. Policy-makers need better understanding of the link between anthropogenic disturbances and wildlife disease hosts at the interface of human society and the natural environment, for example agriculture, forestry and aquaculture. Empirical research is strongly

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

5
1

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 57 publications
(71 reference statements)
0
19
0
Order By: Relevance
“…In the era of ‘Global One Health’, the control of zoonotic diseases in domestic animals becomes even more complex when wildlife hosts are involved (Gebreyes et al., 2014; Miller & Olea‐Popelka, 2013). Anthropogenic disturbance of wildlife populations, whether via habitat destruction or human encroachment, is increasingly cited as a source of spill over of novel or endemic pathogens to humans or livestock (Baker et al., 2022; Murphy et al., 2022); culling of wildlife species can appear an attractive option for disease control (Miguel et al., 2020). Zoonotic tuberculosis is an example of such complexity, with epidemics worldwide involving multiple hosts (Miller & Olea‐Popelka, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In the era of ‘Global One Health’, the control of zoonotic diseases in domestic animals becomes even more complex when wildlife hosts are involved (Gebreyes et al., 2014; Miller & Olea‐Popelka, 2013). Anthropogenic disturbance of wildlife populations, whether via habitat destruction or human encroachment, is increasingly cited as a source of spill over of novel or endemic pathogens to humans or livestock (Baker et al., 2022; Murphy et al., 2022); culling of wildlife species can appear an attractive option for disease control (Miguel et al., 2020). Zoonotic tuberculosis is an example of such complexity, with epidemics worldwide involving multiple hosts (Miller & Olea‐Popelka, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Given these initial findings, and the limitations with the current study’s approach, a matched case-control study of Irish farms exposed to forest clearance was developed [ 29 ]. The study design was designed to gain insights into how local ecological conditions modulated bTB risk at various spatio-temporal scales after a clearfell event.…”
Section: Discussionmentioning
confidence: 99%
“…That study found an association between clearfelling forestry and cattle herd bTB risk; however, the effects could be either positive or negative, dependent on many factors, e.g., the size of the clearfell (in hectares), the distance to the farm, the time elapsed since the clearfell occurred and, perhaps most importantly, the area (in hectares) of natural habitats around the farm, which may act as refugia for wildlife vectors. The changing dynamics of bTB risk over space and time shown by Murphy et al [ 29 ] and the findings of the present study clearly demonstrate the complexity of elucidating disease risk in response to ecological disturbance and highlight the need for these challenges to be approached from multiple different perspectives (e.g., ecological, epidemiological, veterinary science), with different study designs, to build a complete understanding of these processes in order to inform policy and management of the agro-ecological episystem in Ireland.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low spatial resolution areal counts are commonly available for wildlife (e.g., number of animals harvested or simply observed for a region, province, county, or other administrative boundary), however these data lack spatial resolution, limiting their use in preference of higher resolution data such as observations from sophisticated tracking devices e.g., GPS, VHF (Thomas et al 2013). Unfortunately, systematic monitoring schemes take time to become established, demand a significant amount of time and financial investment to remain viable, and require careful governance of the programme and curation of the data – facets that often-become barriers to the establishment and continuation of a successful systematic monitoring scheme (Lindenmayer and Likens, 2009; Murphy et al 2022).…”
Section: Introductionmentioning
confidence: 99%